(untitled) (Revista Apotheke, 2018)
By mapping the actions and knowledge contained in my artist practices I have understood the montage as an important element in the process of creating a collage and, consequently, in the work with images. Guided by the will to effect a thought connected with my experience, in this text I try to pay attention to the principles that the montage of a collage makes possible, approaching the notion of atlas of images developed by Aby Warburg where I am offered a visual configuration of thoughts by where the exchange, circulation and survival (DIDI-HUBERMAN, 2013) of the images.